3x-3+45=-3x

Simple and best practice solution for 3x-3+45=-3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-3+45=-3x equation:


Simplifying
3x + -3 + 45 = -3x

Reorder the terms:
-3 + 45 + 3x = -3x

Combine like terms: -3 + 45 = 42
42 + 3x = -3x

Solving
42 + 3x = -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
42 + 3x + 3x = -3x + 3x

Combine like terms: 3x + 3x = 6x
42 + 6x = -3x + 3x

Combine like terms: -3x + 3x = 0
42 + 6x = 0

Add '-42' to each side of the equation.
42 + -42 + 6x = 0 + -42

Combine like terms: 42 + -42 = 0
0 + 6x = 0 + -42
6x = 0 + -42

Combine like terms: 0 + -42 = -42
6x = -42

Divide each side by '6'.
x = -7

Simplifying
x = -7

See similar equations:

| -6x+6(7x-15)=198 | | 6(5x+1)=5x-8X | | 3(4x+3)=2-5(7-x) | | 164x-82=738 | | 7(3x+1)=3x-8x | | 0.02x+0.5=0.35x+1.2 | | 5x+1=-13x+15 | | 2z+96=15z-85z | | 21x^2=7x | | x^2+2i=0 | | an=5n-8 | | -9+90=9x-90 | | 5x-95=x | | -8y-2=-7y-7 | | 3-4x+6-7=42 | | lnx=0.85 | | x^2+12x=540 | | 4(x-3)+2x=10 | | 1+15=-4(4x-4) | | 7x+9y=3+9x | | 30x^2+273x-270=0 | | m+11/8=8 | | 1+15=4(4x-4) | | 15x-5=25x+3 | | 2(x-3)+10=18 | | -4(x+1)-14=16+2 | | x+7+4x-3=3x+x-2x+16 | | 5k-3/(-3) | | y=-(1/3)x | | y=7000x+b | | 5k-3/3 | | 5k-3/-33 |

Equations solver categories